Mode selection of post-earthquake recovery and reconstruction of traditional villages using dependency analytic process: taking Xiluo-Buzi village in the 2022 M6.8 Luding earthquake as an example - Huang, Chao; Qiu, Jian; Huang, Tianmin (Frontiers in Public Health, 2023)
Traditional villages represent invaluable historical and cultural heritage sites. The choice of postearthquake recovery and reconstruction (PERR) mode directly impacts the preservation of village cultural heritage and the direction of post-disaster reconstruction. This study presents a summary of three PERR modes and establishes an evaluation index system for selecting PERR modes for traditional villages. In view of the interrelationship of the indicators, this study introduces the Dependency Analytic Process (DAP), which is applicable for comprehensive evaluations involving multiple factors, particularly in situations where it is challenging to differentiate the importance of the indicators. This novel method offers a promising approach to determining the weight vector. Using this approach, a model for selecting PERR modes for traditional villages is formulated, and an empirical analysis is conducted using the case of the earthquake-stricken area of Xieluo-buzi Village in the 2022 M6.8 Luding earthquake. The analysis discusses the selection of PERR modes for traditional villages, and the results can serve as a foundation for guiding the selection of PERR modes for traditional villages and informing post-disaster reconstruction decision-making.Evaluation for Selecting PERR mode for Traditional VillageThe post-disaster reconstruction modes in various parts of the world mainly include on-site reconstruction, off-site reconstruction, partial on-site, and partial off-site reconstruction (14-16).Regard to the PERR modes for traditional villages, the authors have summarized the relevant research results (Table 1): Table 1. Overview of existing research on PERR modes for traditional villages